Combined chlorination and nanofiltration to enhance removal efficiencies of sulphonamide in simulated wastewater / Mohd Redzuan Ramli - Mohd Redzuan, Ramli (2015)
Rapid advancement in healthcare and manufacturing industries has resulted in the introduction of new potentially harmful chemicals such as endocrine disrupting chemicals (EDCs) and pharmaceutically active compounds (PhACs) from wastewater produced by these industries into the water bodies. Presence of these types of compound at the final stages of the water treatment system may potentially render the disinfection process ineffective due to the formation of dangerous by-products that have higher toxicity compared to their parent compounds. In this study, the effectiveness of a system that combined two methods of treatment, namely chlorination and nanofiltration was compared with the conventional treatment method where the two systems are separately employed. Four types of sulphonamide derivatives (sulfanilamide (SNM), sulfadiazine (SDZ), sulfamethoxazole (SMX), and sulfadimethoxine (SDM)) were chosen as EDCs model. Sulphonamide is a synthetic antibiotic that is widely used by human as veterinary medicine especially in poultry farming. Using benchscale nanofiltration system, nanofiltration experiments were conducted in three different modes; 1) Pre-chlorination system where the Free Active Chlorine (FAC) was added to the membrane influent (i.e. chlorination followed by nanofiltration), 2) Post-Chlorination system where the FAC was added to the membrane effluent (i.e. chlorination after nanofiltration), and 3) Simultaneous system where the chlorination was subjected to the membrane feed during nanofiltration process (simultaneous chlorination and nanofiltration). Chlorination of sulphonamide at three different pH yields different reaction rates that varied greatly with pH 5.6 showing the highest rate compared to pH 7.2 and pH 10. From the first order plot of chlorination kinetics, the reactivity of sulphonamide with free chlorine is SDM > SNM > SMX > SDZ. Rejection rate for nanofiltration of sulphonamide derivatives without the presence of FAC are 12.5%, 69.5%, 75.5%, and 79.0% for SNM, SDZ, SMX, and SDM, respectively. Overall,removal efficiencies of sulphonamide for pre-chlorination-nanofiltration system (>99.5%) and simultaneous system (>99.0%) are higher compared to the conventional nanofiltration-post-chlorination system (>89.5%). However, in the case of limited FAC ([FAC]0 : [sulphonamide]0 ≤ 1), removal efficiency for nanofiltration-post-chlorination system was higher compared to the other two systems due to the prior nanofiltration process that effectively removed 12.5% to 80% of four sulphonamide derivatives and consequently helped reduced the concentration of sulphonamide in permeate. Nanofiltration of reaction by-products in pre-chlorination and hybrid systems showed better results compared to post-chlorination system. Majority of the reactions by-products formed during the chlorination of sulphonamide were found to be higher in molecular weight compared to its original compound although some of the by-products size were smaller than the molecular weight cut-off (MWCO) of nanofiltration membrane employed. The flux for both pre-chlorination and hybrid systems were considerably higher than in the untreated feed system due to the reduction in the concentration of sulphonamide in membrane feed. Continuous exposure of membrane surface to FAC in both hybrid and pre-chlorination system contributed significantly to the increases of permeate flux. The rejection rates of Na+ on used membranes suggest that the membrane used in pre-chlorination system was only slightly degraded from the chlorine attack. FTIR analysis and morphology study on membrane used in simultaneous system indicates that the membrane is significantly damaged.